Design and Implementation of a 16-Electrode Electrical Impedance Tomography Data Acquisition System for Medical Imaging - Aldo Nofrianto; Audy; Aditya Wardani (Telkom University, 2025)
Electrical Impedance Tomography (EIT) is a non-invasive imaging modality that reconstructs the internal resistivity distribution of an object using electrical measurements acquired from boundary electrodes. This paper presents the design, implementation, and experimental validation of a 16-electrode EIT data acquisition system for medical imaging applications. The developed system consists of a signal generator, voltage-to-current converter (VCC), voltage measurement circuit, multiplexer/demultiplexer unit, microcontroller, and image reconstruction algorithm. Experimental evaluations were conducted to assess signal stability, current injection performance, and voltage measurement accuracy. The XR2206 signal generator produced stable output over a frequency range of 1 to 210 kHz with an output impedance of 0.0784 kohm. The LF412-based amplifier demonstrated linear operation up to 50 kHz, while the VCC generated stable injection currents ranging from 0.3 to 2 mA for load variations between 100 to 2000 ohms, with optimal stability at 10 kHz. Data acquisition was performed using the adjacent method on a 16-electrode phantom containing bovine bone as a resistive object. Image reconstruction using the iterative Newton-Raphson method with Tikhonov regularization successfully identified the position and boundaries of the object. The optimal imaging performance was achieved at an injection current of 0.3 mA and a frequency of 10 kHz. Overall, the system shows reliable imaging.